The effect of environmental gradient on biodiversity and similarity of invertebrate communities in eelgrass (Zostera marina) beds. Issue 1 (22nd January 2020) - Namba, Mizuho; Hashimoto, Marina; Ito, Minako; Momota, Kyosuke; Smith, Carter; Yorisue, Takefumi; Nakaoka, Masahiro
Abstract: Environmental filtering and dispersal limitation are important processes within the metacommunity concept. Non‐random species turnover occurs in places where environmental filtering plays the key role in determining local community structure, whereas dispersal limitation causes nested patterns of species assemblages organized by non‐random colonization processes. However, factors that modify the relative importance of these processes remain unclear for many ecosystems. We tested whether salinity gradient affect the relative importance of environmental filtering and dispersal limitation for structuring epifaunal and infaunal communities in three lagoons in Hokkaido, Japan, that have different salinity gradients. Specifically, we compared patterns of species diversity and similarity of eelgrass‐associated invertebrate assemblages across space. Beta diversity (i.e., species turnover among different sites in each lagoon) was highest in Akkeshi, the lagoon with the salinity gradients. Variation partitioning of similarity components showed that spatial variation in the community assemblage pattern was mostly explained by environmental filtering in Akkeshi, but that it was explained more by species dispersal patterns and the difference in eelgrass biomass and shoot density in Notoro and Saroma, the lagoons without clear salinity gradient. Redundancy analysis showed that spatial variation in community structure was related to salinity and eelgrass biomass in Akkeshi, and to eelgrass aboveground biomass in Notoro and Saroma. Our findings highlight the effects of environmental heterogeneity on beta diversity and community structure and indicate that environmental gradients can be a key factor causing a shift in the relative importance of different metacommunity processes and the role of the foundation species in provisioning habitat. Abstract : We examined the relative importance of environmental filtering and dispersal‐limitation within a lagoonal ecosystem by comparing eelgrass beds from lagoons with a steep salinity gradient and a small salinity gradient.